Кон Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape: Për Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape - Badarevski, Bobi; Ahmeti, Lindita (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Bobi Badarevski | Боби Бадаревски Title (Macedonian): Кон Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape Title (Albanian): Për Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape Translated by (Macedonian to Albanian): Lindita Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 231-232 Page Count: 2 Citation (Macedonian): Боби Бадаревски, „Кон Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape“, Идентитети: списание за политика, род и култура, т. 3, бр. 1 (лето 2004): 231-232. Citation (Albanian): Bobi Badarevski, „Për Cheryl Brown Travis (Ed.), Evolution, Gender, and Rape“, përkthim nga Maqedonishtja Lindita Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 1 (Summer 2004): 231-232.